SCIENCE – SOURCE FOR TECHNOCRACY AND POLITICAL POWER - Brigadier-general (ret.) Professor Mircea UDRESCU, Ph.D; Colonel (ret.) Professor Eng. Eugen SITEANU, Ph.D (Annals: Series on Military Sciences, 2022)
Technocracy represents a political and sociological orientation of use in the general interest of established elites based on which the leading role in society must be assigned to engineers, technicians and specialists from the various fields of science. In other words, technocracy would be a form of government whereby political decision-making power belongs to technicians and scientists called technocrats. Technocracy thus appears as a notion of maximum generalization that suggests that leadership positions at different organizational levels be entrusted on the basis of scientific competence criteria and not on political criteria. This notion has its origin in the Greek language where the word "tekhne" means skill and "kratos" - decision-making power, and William Henry Smith guaranteed that the 1929s would not have had catastrophic consequences if society had been led by a scientific elite.